Effects of spermicidal extracts of Ananas comosus (pineapple) and Sapindus saponaria (jaboncillo) on cell viability, cytotoxicity and apoptosis (2013)
ABSTRACT: Introduction: there are natural products from different fruits and plants that are effective as spermicides, but it is important that they should have little or no cytotoxic effect on epithelial cells. Currently available spermicides with nonoxynol-9 cause vaginal irritation and damage to the vaginal mucosa, the uterine epithelium, and the microbial flora of the vagina. Objective: to elucidate the effect on cell viability, cytotoxicity and apoptosis of spermicidal extracts of Ananas comosus (L.) Merr. and Sapindus saponaria L. over HeLa cell line. Methods: both extracts were evaluated on HeLa cell line using the novel ApoTox-Glo™ Triplex Assay to determine whether cell viability, cytotoxicity and apoptosis were affected. Results: it was determined that treatment with Sapindus saponaria and Ananas comosus extracts initially affected cell viability, but the latter tended to be restored. There was a sign of cell apoptosis that also tended to decrease over time. Conclusions: extracts of Sapindus saponaria and Ananas comosus may affect the survival of cells at the beginning, but these can continue replicating over time. There was a sign of cell apoptosis that also tended to decrease over time. Something similar happened to cell cytotoxicity, indicating that although the extracts may affect the survival of cells at the beginning (6 hours of treatment), these can continue dividing over time.